Constitutively Active Mutant gp130 Receptor Protein from Inflammatory Hepatocellular Adenoma Is Inhibited by an Anti-gp130 Antibody That Specifically Neutralizes Interleukin 11 Signaling - Sommer, Jan (American Society for Biochemistry and Molecular Biology, 2012)
Ligand-independent constitutively active gp130 mutants were described to be responsible for the development of inflammatory hepatocellular adenomas (IHCAs). These variants had gain-of-function somatic mutations within the extracellular domain 2 (D2) of the gp130 receptor chain. Cytokine-dependent Ba/F3 cells were transduced with the constitutively active variant of gp130 featuring a deletion in the domain 2 from Tyr-186 to Tyr-190 (gp130ΔYY). These cells showed constitutive phosphorylation of signal transducer and activator of transcription-3 (STAT3) and cytokine-independent proliferation. Deletion of the Ig-like domain 1 (D1) of gp130, but not anti-gp130 mAbs directed against D1, abolished constitutive activation of gp130ΔYY, highlighting that this domain is involved in ligand-independent activation of gp130ΔYY. Moreover, soluble variants of gp130 were not able to inhibit the constitutive activation of gp130ΔYY. However, the inhibition of constitutive activation of gp130ΔYY was achieved by the anti-gp130 mAb B-P4, which specifically inhibits gp130 signaling by IL-11 but not by other IL-6 type cytokines. IL-11 but not IL-6 levels were found previously to be up-regulated in IHCAs, suggesting that mutations in gp130 are leading to IL-11-like signaling. The mAb B-P4 might be a valuable tool to inhibit the constitutive activation of naturally occurring gp130 mutants in IHCAs and rare cases of gp130-associated hepatocellular carcinoma.